The homewreckers [large type] - Andrews, Mary Kay, 1954- (Thorndike Press large print core series., 2022)
"Hattie Kavanaugh went to work helping clean up restored homes for Kavanaugh & Son Restorations at eighteen, married the boss's son at twenty, and was only twenty-five when her husband was killed in a motorcycle accident. Determined to continue the business, she takes the life insurance money, buys a small house, flips it, then puts the money into her next project. But that house is a disaster and a money-loser, which rocks her confidence. Then, Hattie gets an opportunity to star in a beach house renovation reality show called The Homewreckers, cast against a male lead who may be a love interest, or may be the ultimate antagonist. It's a question of who will flip, and who will flop, and will Hattie ever get her happily-ever-after"--